Prognostic Value of Programmed Cell Death Ligand-1 Expression in Nasopharyngeal Carcinoma: A Meta-Analysis of 1,315 Patients - Liu, Xiaofeng; Shan, Chunguang; Song, Yingluan; Du, Juan (Frontiers in Oncology, 2019)
Background: The prognostic value of programmed cell death ligand-1 (PD-L1) in patients with nasopharyngeal carcinoma (NPC) remains controversial. Therefore, we conducted this meta-analysis to understand the role of PD-L1 in NPC. Method: We searched PubMed, Embase, Web of Science, and Cochrane Library up to April 2019. We determined the pooled hazard ratio (HR) and 95% confidence intervals (CIs) to assess the relationship between PD-L1 and various survival outcomes. Begg’s funnel plot was used to assess any publication bias. Results: Eleven studies involving 1315 patients were included in this meta-analysis. For overall survival (OS), the HR was 1.48 and 95% CI was 1.00–2.18 (p=0.049). For disease-free survival (DFS), the HR was 1.51 and 95% CI was 0.85–2.69 (p=0.162). For distant metastasis-free survival (DMFS), the HR was 1.75 and 95% CI was 0.64–4.79 (p=0.277). For local recurrence-free survival (LRFS), the HR was 0.67 and 95% CI was 0.06–8.16, (p=0.756). The results of prognosis of PD-L1 and OS were more significant after sensitivity analysis. The pooled odds ratio indicated that PD-L1 expression was not associated with T stage, N stage, M stage, overall stage, sex, age, smoking, or alcohol intake. No publication bias was found. Conclusion: Our meta-analysis showed that PD-L1 overexpression in NPC was associated with a poor OS and may be useful as a novel prognostic factor for NPC.